PENGARUH PENGAWASAN TERHADAP PENINGKATAN KINERJA PEGAWAI DI KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN SIDENRENG RAPPANG - Winda Ayu Lestari; Muhammad Ikbal; Pratiwi Ramlan (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
Performance in the Office of the Personnel and Human Resources Development Agency of Sidenreng Rappang Regency. The population in this study were 43 people. The sample is 43 people. The chili dance technique used is purposive sampling. This type of research is descriptive quantitative. Data collection techniques used are observation, interviews, questionnaires, literature study. The data analysis technique used is descriptive statistics and The results showed that the supervision was in the good category with a percentage of 65.5%. The performance is in the poor category with a percentage of 60%. Based on the value of t count> t table or 9.411> 2.019 then H0 is rejected and Ha is accepted, which means it is significant. So, the effect of supervision has a significant effect. Supervision Improvement of Employee Performance in the Office of the Personnel and Human Resources Development Agency of Sidenreng Rappang Regency with a percentage of the contribution of influence of 68.4%.